2009
DOI: 10.1213/ane.0b013e3181baf506
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Preconditioning Ameliorates Endotoxin-Induced Acute Lung Injury and Mortality in Rats

Abstract: Isoflurane preconditioning can attenuate pulmonary proinflammatory cytokine release and decrease the mortality induced by severe sepsis. Early protection seems to be mediated partly through inhibition of iNOS-NO pathway activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 36 publications
1
37
0
6
Order By: Relevance
“…4), which are pro-inflammatory, pro-fibrogenic and pro-angiogenic mediators. These findings are consistent with previous studies in which volatile anaesthetics reduced TNF-a [15][16][17][18][19][20][21], exerting antiinflammatory and organ-protective effects in ARDS models, even after a brief exposure [19]. The immunomodulatory effects of sevoflurane may be attributable to several mechanisms: (1) inhibition of synaptic transmission by activation of type-A gamma-aminobutyric acid (GABA A ) receptors in neurons [40], lung airways and alveolar cells [41], thus improving oxygenation and attenuating lung inflammation [15]; (2) reduction in TNF-a-induced endothelial permeability [42]; and (3) inhibition of TNF-a expression and inflammatory cytokine production through intracellular pathways [43].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4), which are pro-inflammatory, pro-fibrogenic and pro-angiogenic mediators. These findings are consistent with previous studies in which volatile anaesthetics reduced TNF-a [15][16][17][18][19][20][21], exerting antiinflammatory and organ-protective effects in ARDS models, even after a brief exposure [19]. The immunomodulatory effects of sevoflurane may be attributable to several mechanisms: (1) inhibition of synaptic transmission by activation of type-A gamma-aminobutyric acid (GABA A ) receptors in neurons [40], lung airways and alveolar cells [41], thus improving oxygenation and attenuating lung inflammation [15]; (2) reduction in TNF-a-induced endothelial permeability [42]; and (3) inhibition of TNF-a expression and inflammatory cytokine production through intracellular pathways [43].…”
Section: Discussionsupporting
confidence: 93%
“…Some case reports have described a beneficial action of anaesthetics in refractory asthma [12][13][14], and studies have demonstrated their anti-inflammatory effects in experimental [15][16][17][18][19] and clinical [20,21] acute respiratory distress syndrome (ARDS) protocols. We have previously reported that sevoflurane promoted bronchodilation and reduced atelectasis in experimental allergic asthma [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some literature reports that volatile anaesthetics showed protective effects against lung injury 9-13. In a male mouse model of endotoxin-induced lung injury, isoflurane pre-treatment significantly attenuated PMN recruitment into the injured lung 12.…”
Section: Discussionmentioning
confidence: 99%
“…Liu and colleagues10, 11 reported the administration of isoflurane before ischaemia and during reperfusion inhibited IR-induced isolated rabbit lung injury and demonstrated that not only isoflurane but also sevoflurane administered before ischaemia attenuated IR-induced injury in isolated rat lungs. More recently, Reutershan12 and Li13 documented the protective pre-treatment effects by isoflurane against endotoxin-induced lung injury in mouse and rat models.…”
Section: Introductionmentioning
confidence: 99%
“…isoflurane, sevoflurane) are known to possess anti-inflammatory properties and have been shown to prevent sepsis-mediated ALI, 7 as well as ischemia/ reperfusion injury following cardiac bypass (CBP) procedures. 8 These volatile gasses are known to prevent neutrophil adhesion to the endothelium, 9,10 but the exact mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%